ANALISIS KETERAMPILAN BERPIKIR KREATIF DI MTs NEGERI 3 KOTA SURABAYA - Inayah, Nailil; Mukaromah, Sa’ida Umi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
21st Century Challenges encourage students to develop creative thinking skills, because creative thinking skills can be used to solve problems or improve thinking skills. Apart from that, the Merdeka curriculum also emphasizes creative thinking skills. This is because it is the basis for increasing students"™ understanding. This research aims to determine the achievement of each indicator of creative thinking and determine and determine each category of indicators of creative thinking skills. The subjects of this research were 28 class VII student at MTs Negeri 3 Surabaya City. The data collection technique uses an essay test. The research results show that creative thinking skills at MTs Negeri 3 Surabaya City are classified as less creative. The percentages per indicator of creative thinking are 38% fluency, 21% flexibility, 35% original thinking, and 37% elaboration. The lack of creative thinking skills in students can be corrected by updating the learning model, so that students are not too teacher-centred when learning.